The Influence Of Lifestyle, Brand Image, And Product Design On Smartphone Purchase Decisions (Study On Students In Dki Jakarta) - Harits Abyan Aufa (Publikasi Indonesia, 2023)
This study uses a quantitative method with the aim of proving the influence of Lifestyle, Brand Image, and Product Design directly and indirectly on Purchase Decision. This study used 150 respondents from student of Smartphone Top Brand 2023 in DKI Jakarta as primary data, and secondary data researchers obtained through various references related to research. Data were collected using purposive sampling technique and analyzed using descriptive and inferential analysis techniques with the help of SmartPLS software. So that data processing obtains the results that (1) Lifestyle has a positive and significant effect on Purchase Decision, (2) Brand Image has a positive and significant effect on Purchase Decision, (3) Product Design has a positive and significant effect on Purchase Decision, 4) Lifestyle, Brand Image, and Product Design both have a positive effect on Purchase Decision.